International Transmission of Environmental Policy: A New Keynesian Perspective - Giovanni Ganelli; Juha Tervala (Aboa Centre for Economics (ACE), 2010)
In this paper we examine the international transmission of environmental policy using a New Keynesian model of the global economy. We first consider the case in which the quality of the environment affects utility, but not productivity. This allows us to look at the trade-off between environmental quality and output. We then consider the case in which the quality of the environment increases productivity but does not affect utility. Our main results show that in both cases a unilateral implementation of a more stringent environmental policy by the domestic country raises foreign welfare under a benchmark parameterization. However, since this policy can have a negative impact on domestic utility but a positive one on world utility, an international coordination problem can arise in the implementation of environmental policy: no country will have an incentive to implement environmental reforms if there is a possibility that its trading partners will do so.
Keywords: E30; F41; F42; Q50; 330; Environmental Economics; Environmental Policy; International Policy Coordination; Open Economy Macroeconomics